Autism Risk Gene MET Variation and Cortical Thickness in Typically Developing Children and Adolescents - Hedrick, Alexis (2012)
MET receptor tyrosine kinase (MET) has been proposed as a candidate risk gene for autism spectrum disorder (ASD) based on associations between MET polymorphisms and ASD diagnosis, as well as evidence from animal studies that MET protein may regulate early development of cortical regions implicated in the neurobiology of ASD. The relevance of differences in MET signaling for human cortical development remains unexamined, however. We sought to address this issue by relating genotype at a functional single nucleotide polymorphism within the MET promoter (rs1858830, G→C), to in vivo measures of cortical thickness development derived from 222 healthy children and adolescents with 514 longitudinally acquired structural MRI brain scans between ages 9 and 22 years. We identified a statistically significant, developmentally fixed, and stepwise CT reduction with increasing C allele dose in superior and middle temporal gyri, ventral pre- and post-central gyri, and anterior cingulate bilaterally, and in the right fronto-polar cortex. We were also able to demonstrate that mean CT within these cortical regions showed a statistically significant reduction with increasing scores on a continuous measure of autistic traits (the Social Responsiveness Scale). The cortical regions highlighted by our analyses are not only established areas of MET expression during prenatal life, but are also key components of the “social brain” which have frequently shown structural and functional abnormalities in autism. Our results suggest that genetic differences in the MET gene may influence the development of cortical systems implicated in the neurobiology of ASD